Transforming theory for a transforming world: An essay in review of Anna Stetsenko's The Transformative Mind: Expanding Vygotsky's Approach to Development and Education. (June 2020) - Collins, Chik; Jones, Peter E.; McCrory, Marjorie
Abstract : Critical social science has long struggled adequately to theorise social change and transformation. Today, however, the questions of the moment are perhaps more clearly than ever all about those things. In this gap arise profound challenges – both theoretical and political. Anna Stetsenko's The Transformative Mind (2017) offers a major contribution to the reorientation of critical social science – providing foundations which ground and catalyse our urges to make our humanity in the struggle to create new forms of social relating, worthy of our human nature.